Good Corporate Governance and Corporate Social Responsibility: Does Company Size Moderate? - Fernanda Aditya Putra, Ferry; Harjito, Yunus; Rahman Siddiq, Faiz; Binti Inang, Monika (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the effect of Good Corporate Governance on Corporate Social Responsibility with Company Size as a Moderating Variable. The population in this study were Mining Companies listed on the Indonesia Stock Exchange in 2018-2022, the sample obtained was 265 samples from 53 companies. Sampling using Purposive Sampling technique. This study uses multiple linear regression analysis techniques and Moderated Regression analysis with the help of the SPSS program. The results showed that Good Corporate Governance proxied by the Board of Commissioners has a significant negative effect on Corporate Social Responsibility, and Good Corporate Governance proxied by the Audit Committee has no effect on Corporate Social Responsibility, while Good Corporate Governance proxied by Institutional Ownership has a significant positive effect on Corporate Social Responsibility. Company size proxied using total assets is not proven to moderate the relationship between the effect of Good Corporate Governance on Corporate Social Responsibility.